Ergospirometry and Echocardiography in Early Stage of Heart Failure with Preserved Ejection Fraction and in Healthy Individuals - Garcia,Eduardo Lima (2015)
AbstractBackground:Heart failure with preserved ejection fraction is a syndrome characterized by changes in diastolic function; it is more prevalent among the elderly, women, and individuals with systemic hypertension (SH) and diabetes mellitus. However, in its early stages, there are no signs of congestion and it is identified in tests by adverse remodeling, decreased exercise capacity and diastolic dysfunction.Objective:To compare doppler, echocardiographic (Echo), and cardiopulmonary exercise test (CPET) variables - ergospirometry variables - between two population samples: one of individuals in the early stage of this syndrome, and the other of healthy individuals.Methods:Twenty eight outpatients diagnosed with heart failure according to Framingham’s criteria, ejection fraction > 50% and diastolic dysfunction according to the european society of cardiology (ESC), and 24 healthy individuals underwent Echo and CPET.Results:The group of patients showed indexed atrial volume and left ventricular mass as well as E/E’ and ILAV/A´ ratios significantly higher, in addition to a significant reduction in peak oxygen consumption and increased VE/VCO2 slope, even having similar left ventricular sizes in comparison to those of the sample of healthy individuals.Conclusion:There are significant differences between the structural and functional variables analyzed by Echo and CPET when comparing two population samples: one of patients in the early stage of heart failure with ejection fraction greater than or equal to 50% and another of healthy individuals.